Optimization and Improvement of the Quality of Teaching and Learning the Qur'an Thru Mentoring at the TPQ of Juwet Village Jombang - Dian Erwanto; Sofuan Jauhari; Rifky Rosian Annur; Muslikh Ubaidillah; Muhammad Maulana Al-Farizy; Muhammad Afif Hadiansyah (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The low level of Qur’anic literacy at the elementary education level remains a fundamental problem hindering the internalization of religious values among the younger generation. In rural areas, this phenomenon is escalated by a shortage of competent educators and the dominance of monotonous, conventional pedagogical methods. Such conditions lead to stagnation in learning outcomes, necessitating strategic intervention through community empowerment programs. This research aims to revitalize the Qur’anic Education Center (TPQ) in Juwet Village to ensure a more effective, adaptive, and sustainable religious knowledge transmission process. Methodologically, this study adopts a qualitative approach within a Participatory Action Research (PAR) framework. The researchers were actively involved in instructional dynamics to empirically identify barriers. Grounded in transformative education theory, strengthening teacher capacity is positioned as the primary instrument of change. Data were gathered through participant observation, in-depth interviews, and periodic evaluations of students’ tajwid competence and reading fluency to establish a continuous improvement cycle. The findings indicate that intensive mentoring interventions significantly enhance student learning motivation and accelerate material comprehension. Furthermore, the program successfully optimized the standardization of teachers’ recitation quality through the implementation of systematic and measurable instructional methods. The implications of this study emphasize that a sustainable mentoring model is a key determinant in transforming the quality of religious education in rural regions. The success in this research site serves as a potential prototype for similar institutions in efforts to eradicate Qur'anic illiteracy and comprehensively improve Islamic literacy